The human resource model of field officers for irrigation modernization in Indonesia: A case study of the rentang irrigation area - Ernawati, Ernawati; Soekarno, Indratmo; Siswanto, Joko; Suryadi, Yadi (Edelweiss Applied Science and Technology, 2025)
The government of Indonesia has undertaken the modernization of irrigation systems as one of its key initiatives to achieve food security. This modernization is supported by five main pillars: water availability, irrigation infrastructure, irrigation management, irrigation institutions, and human resources, which serve as the key actors in irrigation management. To assess the readiness for irrigation modernization, Indonesia employs the Irrigation Modernization Readiness Index (IKMI). Among the five pillars, the human resource component consistently scores lower than the others. However, human resources are arguably the most critical factor in the successful implementation of irrigation modernization. This study explores a model for enhancing the human resource component, specifically focusing on field officers such as irrigation technicians (mantri/juru), dam operation officers, and water gate officers. A mixed-method approach was employed, combining quantitative surveys, qualitative interviews, and focus group discussions with 100 field officers in the Rentang Irrigation Area. The findings reveal that the IKMI score for Rentang is 66.9, categorized as “sufficient,” with socio-economic conditions being the weakest aspect. To address this, a conceptual framework is proposed, outlining three progressive stages of readiness: sufficient, adequate (early, mid, and advanced), tailored to the specific needs of the region. The study concludes that structured capacity-building interventions, particularly targeted training programs, are essential to elevate human resource readiness and support the broader goals of irrigation modernization and national food security.